Shari`ah objectives of marriage: the significance in stabilizing families - Haneef, Sayed Sikandar Shah (LexisNexis, 2013)
Marriage as ordained by God, is supposed to provide a man and a woman with a homely abode for companionship, peace and intimacy, mutual love, affection, gaining comfort and attaining psycho-emotional well-being. This is important as Islam`s grand design is to create quality Ummah out of loving , harmonious and emotionally nurturing home environment -which begins with the marriage between two members of the opposite sexes among Allah`s servants. To achieve the above goal, Islam enacts a well-structured system of law and ordains a binding code of reciprocal marital obligation that is binding on both the spouses. Nevertheless, today it seems that some Muslims` vision of marriage has become either blurred or colored by fleeting hedonistic philosophy. The very fact that the rate of divorce -with its attendant devastating effect on children, among Muslims, the world over is staggeringly on the rise and even our Islamic family laws are incapable of containing its wreaking havoc on our home is symptomatic of such loss of vision on our part. Therefore, to remedy the situation, experts both in the Muslim and non-Muslim world, look for ways of strengthening the marriages. To me, the reorientation of Muslims about the philosophy behind marriage life, if internalized and lived by, is the key to successful implementation of any human initiated endeavors in this direction. Accordingly, this paper is an attempt to shed some lights on this aspect of the remedies.